Vigilância genômica de sars-cov-2 na cidade de Fortaleza: caracterização de variantes e fortalecimento do monitoramento epidemiológico - Costa, Thaís de Oliveira (2023)
The emergence of the COVID-19 pandemic has been a catalyst for unprecedented advances in the application of whole-genome sequencing (WGS) techniques focused on genomic surveillance (GS) of SARS-CoV-2 (SC2). The aim is to enhance preventive measures and interventions in the face of viral evolution, as well as to contribute to ongoing scientific progress in the development of new drugs and vaccines. Despite the high number of SC2 genomes in public repositories, there is a bias favoring more advanced technological centers, and a need to standardize coverage and sample representativeness for GS. Therefore, this work aimed to characterize and monitor new SC2 variants in a representative urban center (Fortaleza) during a critical period of the pandemic (Dec/2020 to Dec/2022). During this time, innovative solutions were concurrently developed for monitoring Variants of Concern (VOCs) of SC2. Nasopharyngeal swab samples collected in viral transport medium (VTM) were sent after COVID-19 diagnosis confirmation by RT-qPCR, screened, and sequenced by Next-Generation Sequencing (NGS) on the Illumina platform, as part of collaborative efforts with the Fiocruz Genomic Network. Additionally, complementary methodological approaches to WGS were developed, including: i) implementation of genotyping assays; ii) operationalization of workflow and technical feasibility of reusing residual material from rapid antigen tests (RAT). Mapping specific molecular signatures of variants/lineages under investigation from SC2 genomes in Brazil and Fortaleza deposited in public databases allowed the definition of target regions for VOC screening: i) NSP6: S106del, G107del, F108del; ii) 28262:AACA; iii) S: K417T; iv) S: L452R; v) S: H69del, V70del; and vi) NSP1: K141del, S142del, F143del. These targets served as a basis for customizing/acquiring 8 assays with high sensitivity, specificity, and concordance with WGS (n=3,420). Large-scale application enabled a substantial increase in sample size and obtaining results from heterogeneous biological material. Similarly, implementing an alternative workflow with analytical validation of rapid antigen test (RAT) material resulted in a 3.4x increase in sample coverage for SC2 genomic surveillance during a period of low molecular testing. Viral genetic material recovery, assessed by RT-qPCR, was possible in 93% of the tested RAT aliquots (997/1,072), of which 93.5% generated sequences with phylogenetic lineage definition by WGS (n=347/371). There were no significant differences between results obtained by genotyping and NGS regarding the volume of RAT used for extraction (200μL vs. 50 μL), conservation time (1 day vs. 7 days), or conservation buffer used (Guanidine 4M+EDTA 0.2M vs. Guanidine 4M+Citrate 0.2M). WGS data identified the initial cases of the Gamma VOC (P.1-like), Delta VOC (B.1.617.2-like), and different sublineages of the Omicron VOC (BA.1; BA.2; BA.4; BA.5; BE.9; BQ.1 and XXB). The expansion of emerging lineages, individually or in combination, was associated with successive waves of COVID-19 cases. Integrating WGS results from viral material extracted from VTM (n=4,253) with complementary results from targeted genotyping and analysis of RAT samples allowed maximizing the number of cases analyzed (n=9,860), often reaching the minimum coverage threshold recommended for GS, providing more reliable analyses of the epidemiological scenario. This work highlights the technical-scientific relevance of innovative strategies complementary to WGS in strengthening GS, serving as an exemplary model for monitoring other public health- important pathogens.